Cloning and characterization of two vertebrate homologs of the Drosophila eyes absent gene. - Zimmerman, J E; Bui, Q T; Steingrímsson, E; Nagle, D L; Fu, W; Genin, A; Spinner, N B; Copeland, N G; Jenkins, N A; Bucan, M; Bonini, N M

(untitled) (Genome Research, 1997)
The Drosophila eyes absent (eya) gene plays an essential role in the events that lead to proper development of the fly eye and embryo. Here we report the analysis of two human and two mouse homologs of the fly eya gene. Sequence comparison reveals a large domain of approximately 270 amino acids in the carboxyl terminus of the predicted mammalian proteins that shows 53% identity between the fly sequence and all of the vertebrate homologs. This Eya-homology domain is of novel sequence, with no previously identified motifs. RNA hybridization studies indicate that the mouse genes are expressed during embryogenesis and in select tissues of the adult. Both mouse Eya genes are expressed in the eye, suggesting that these genes may function in eye development in vertebrates as eya does in the fly. The mouse Eya2 gene maps to chromosome 2 in the region syntenic with human chromosome 20q13, and the mouse Eya2 gene maps to chromosome 4 in the region syntenic with human chromosome 1p36. Our findings support the notion that several families of genes (Pax-6/eyeless, Six-3/sine oculis, and Eya) play related and critical roles in the eye for both files and vertebrates.